2012
DOI: 10.1159/000339150
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Presentation of Long QT Syndrome – Evaluation of Prenatal Risk Factors: A Systematic Review

Abstract: Objective: This systematic review evaluated the existence of risk factors for the fetal manifestation of long QT syndrome (LQTS). Methods: Prenatal cardiac findings suggestive of fetal LQTS were studied using 30 English literature reports extracted from the Pubmed database (1979 to December 2011) using the search terms ‘long QT syndrome’, ‘fetal arrhythmia’ and ‘congenital heart disease’. Results: LQTS accounted for 15–17% of fetal bradycardias <110 bpm among fetuses with a normally structured heart. Of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 81 publications
0
22
0
1
Order By: Relevance
“…This is the second report of a patient with TS1 where the arrythmogenic manifestation leads to fetal hydrops [Lo-A-Njoe et al, 2005, patient B]. Fetal hydrops is considered as obligated consequence of heart failure by sustained episodes of fetal AV dissociation and ventricular arrhythmia [Ishikawa et al, 2013]. A genetic explanation for this prenatal presentation of TS1 is difficult because our propositus and the patient of Lo-A-Njoe et al (2005, patient B) shared the same Ca V 1.2 mutation, as in the others previous patients with proven TS1at the molecular level [Lo-A-Njoe et al, 2005;Splawski et al 2006], but without hydrops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the second report of a patient with TS1 where the arrythmogenic manifestation leads to fetal hydrops [Lo-A-Njoe et al, 2005, patient B]. Fetal hydrops is considered as obligated consequence of heart failure by sustained episodes of fetal AV dissociation and ventricular arrhythmia [Ishikawa et al, 2013]. A genetic explanation for this prenatal presentation of TS1 is difficult because our propositus and the patient of Lo-A-Njoe et al (2005, patient B) shared the same Ca V 1.2 mutation, as in the others previous patients with proven TS1at the molecular level [Lo-A-Njoe et al, 2005;Splawski et al 2006], but without hydrops.…”
Section: Discussionmentioning
confidence: 99%
“…LQT syndromes account for 15e17% of fetal bradycardias among fetuses with a normally structured hearts, manifesting also other prenatal signs such as sinus or intermittent bradycardia <110 beats/min, or fetal heart rate <3rd percentile for gestational age, AV block, tachyarrhythmias, or pleural effusion and exceptionally, by fetal hydrops [Ishikawa et al, 2013;Mitchell et al, 2012]. Fetal hydrops as antenatal expression of TS1 has been reported previously in only one instance [Lo-A-Njoe et al, 2005, patient B], since most of them have been usually diagnosed during neonatal period or rarely, in late infancy.…”
Section: Introductionmentioning
confidence: 99%
“…In utero, the fetal presentation of LQTS can manifest as a reduced baseline fetal heart rate <3rd percentile for gestational age or 2 standard deviations below the mean for normal fetuses 1 . In more severe cases, ventricular tachycardia, second-degree AVB, and hydrops may be present 6 . Fetal LQTS has been successfully diagnosed by fMCG 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal rhythms associated with LQTS include torsade de pointes type ventricular tachycardia, 2:1 atrioventricular block, sinus bradycardia <110 beats per minute and a reduced baseline fetal heart rate (110-120 beats per minute), with the latter 2 being the most common. 12 Indeed, neonatal sinus bradycardia has often been noted since the first reports on LQTS and JLNS. However, as fetal manifestations in LQTS have typically been described in cases presenting with fetal arrhythmia, it has not been established whether fetal heart rate in LQTS correlates with genotype per se.…”
Section: Editorial See P 760mentioning
confidence: 99%
“…There was a mean of 9±3 intrauterine heart rate recordings per fetus (range, 1-18) including a mean of 6±3 recordings during the third trimester and onwards (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. When considering all heart rates from week 29 onwards, including heart rates recorded at admission to the delivery ward, pedigree-based association analysis including all founder population cases (n=184) revealed that mean heart rates were lower per added mutation (no mutation, 142±6 beats per minute (n=74); single mutation, 133±8 beats per minute (n=97); double mutations, 111±6 beats per minute (n=13); P<0.0001).…”
Section: Associations Between Intrauterine Heart Rate and Fetal Genotypementioning
confidence: 99%